DFT study adsorption of Hydroxychloroquine for treatment COVID-19 by Al, Si and Si-C doping on carbon nanotube surface: A drug delivery simulation - Al-Sawaff, Zaid H.; Dalgic, Serap Senturk; Kandemirli, Fatma; Monajjemi, Majid; Mollaamin, Fatemeh (Research Square Platform LLC, 2021)
Abstract The aim of this study is to investigate the potential and capability of Al-CNT, Si-CNT, and SiC-NT to detect and adsorb Hydroxychloroquine (C18H26ClN3O) molecular. For this purpose, we considered different configurations for adsorbing Hydroxychloroquine drug on the surface of Al-CNT, Si-CNT, and SiC-NT nanocluster. All considered configurations are optimized using DFT theory at the 6-31G** basis set and M062x level of theory, and then from optimized structures, for each nanoparticle, we selected four stable models for the adsorption of Hydroxychloroquine from (O, N, N, and Cl) sites on the surface the selected nanoparticles. The calculated results indicate that the distance between nanocluster and drug from N site is lower than from all other locations sites for all investigated nanoparticles, and adsorption of Hydroxychloroquine from N site is more favorable especially for the Al-CNT nanotube. The adsorption energy, hardness, softness, and fermi energy results reveal that the interaction of Hydroxychloroquine with Al-CNT is stronger than Si-CNT, and SiC-NT. The results clarify that SiC-NT and Si-CNT are not suitable for Hydroxychloroquine drug adsorption because of the low values of Eads, but Al-CNT is an encouraging adsorbent for this drug as Eads of Hydroxychloroquine/Al-CNT complexes are (-45.07, -15.78, -45.15, -93.53) kcal/mol in the gas phase, and (-43.02, -14.43, -43.86, -88.97) kcal/mol for aqueous solution. The energy gap of the Hydroxychloroquine/Al-CNT system is in the range of 2.32 to 3.84 eV. which is in the range of Al-CNT (2.68). Besides, the HOMO-LUMO orbitals and electrostatic potential (ESP) plots results show that the maximum positive charge is located around the nanocluster surface and the most negative charge is located around the adsorption position and Hydroxychloroquine drug surface. As well, the appropriate and spontaneous interaction between Hydroxychloroquine drug and all nanoparticles was confirmed by investigating the quantum chemical molecular descriptors and solvation Gibbs free energies of all atoms. Al-CNT can be used as an amperometric sensor to detect the Hydroxychloroquine drug molecule. Thus, we propose that the Al-CNT can be a promising candidate as a drug delivery vehicle for Hydroxychloroquine drug molecules.
Keywords: 3. Good health